Housing policies in Hong Kong, China and the People's Republic of China - Victor Jing Li (Asian Development Bank Institute (ADBI), 2016)
This paper analyzes the housing markets and housing policies in Hong Kong, China and the People's Republic of China (PRC). Both markets face housing affordability problems due to limited land supply, for which the solutions vary considerably. Hong Kong, China has adopted a railway and property development model, which involves close collaboration between the government and property developers in compact urban areas, while leaving most greenbelts and surrounding islands underdeveloped. Although the PRC has pledged to maintain a minimum level of basic farmland to feed its large population, this target has often been compromised due to local governments' fiscal constraints and growth concerns. The targets and outcomes of housing policies in both markets are in line with their social welfare systems. Hong Kong, China favors the elderly and the poor, thus housing policies tend to support the lower-income band. The PRC focuses on the young and the rich; hence, most regulative housing policies for the higher-income band have turned out to be unsuccessful. Hong Kong, China also aims to assist public housing tenants to become private homeowners, but its policies help provide housing subsidies, a less effective measure to access owner-occupied housing. On the contrary, the success of Housing Provident Fund in providing mortgage interest rate reduction, which is a more effective measure to access owner-occupied housing, accounts for the high homeownership rate in the PRC.
Keywords: H11; H72; P25; P26; R21; R28; R31; R38; R52; 330; PRC housing market; Hong Kong; China; housing affordability; housing subsidies